Peranan Media Online ”Tanoshiijapanese.com” Sebagai Solusi Pembelajaran Kanji di Masa Pandemi - Kun Makhsusy Permatasari; Alo Karyati (Jurnal Abdimas Adpi Sosial dan Humaniora, 2020)
The COVID-19 pandemic has changed all of our activities and lifestyles. Work, study, socializing and all activities related to physical contact all change. This includes teaching and learning activities. The teaching and learning activities that we have been doing in the classroom, during this pandemic, require all activities to be carried out from home. This automatically changes the habits of both the teacher and the students being taught. The Covid-19 pandemic is not only happening in Indonesia, but is evenly distributed throughout the world. Therefore, there needs to be media that can be used as a means for teaching and learning activities during this pandemic. Based on this, the researchers tried to use online media "tanoshiijapanese" as a learning solution during online lectures. This service activity was carried out on two campuses, namely Darma Persada University and Pakuan University with 43 fourth semester students as participants. This activity aims to determine whether the use of online media “tanoshiijapanese.com is appropriate as a solution for online teaching. Then, to evaluate the activities, data collection was carried out through observation, questionnaires and interviews using google form. The data analysis technique uses graphs from google form. The results of this study are expected to be useful for kanji teachers who will teach online.